Knowledge, attitude and practice regarding COVID-19 among doctors and nurses at a tertiary care maternity hospital in Nepal - Ansari, Shaheen Naaz; Ansari, Imran; Jha, Meena; Upreti, Rakshya (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Knowledge, attitude, and practice (KAP) survey provides a suitable format to evaluate existing programs and to identify effective strategies for behavior change in society. This study aimed to investigate and compare KAP concerning COVID-19 among Health Care Professionals (HCPs) at Paropakar Maternity and Women’s Hospital (PMWH).Method: This was a cross sectional descriptive study conducted in HCPs (doctors and nurses) of PMWH, Nepal, from May to June 2020. A pre-validated questionnaire was used to access the objectives where knowledge and attitude score was 10 each and practice score was 20. Collected data was entered in Microsoft excel spreadsheet and analyzed using IBM SPSS software and p-value < 0.05 was taken as statistically significant.Result: A total of 168 doctors and nurses responded to the survey, of which 112 (66.6%) were in 25-34 years of age group, 87.5% females, and 61.9% nurses. Mean score for knowledge, attitude and practice score was 5.8 (out of 10), 8.1 (out of 10) and 17.4 (out of 20) respectively. The score was significantly different among doctors and nurses in ‘knowledge’ (p=0.000) and ‘attitude’ categories (p = 0.006). There was no significant difference in ‘practice’ scores (p = 0.664).Conclusion: Doctors and nurses of PMWH have positive attitude and good practice towards COVID-19. This characteristic can prove handy in bringing about useful behavioural changes and promoting safe practices while managing maternity patients in this hospital.